2017
DOI: 10.1093/cid/cix036
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prophylaxis for Cryptococcosis With Fluconazole in Human Immunodeficiency Virus–Infected Patients With CD4 T-Cell Counts <100 Cells/µL and Receiving Antiretroviral Therapy

Abstract: A prospective observational cohort study was conducted in 302 human immunodeficiency virus-infected patients who had a CD4 T-cell count <100 cells/µL and negative serum cryptococcal antigen initiating antiretroviral therapy in a resource-limited setting. During 2-year follow-up, there were no differences of survival rates and occurrences of newly diagnosed cryptococcosis between patients with and without fluconazole for primary prophylaxis of cryptococcosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In a recent two-year prospective observational cohort study conducted by Sungkanuparph et al [ 87 ] in Thailand, 302 HIV–infected patients who had a CD4 T-cell count < 100 cells/µL and negative serum cryptococcal antigen initiating antiretroviral therapy were enrolled. Five patients developed cryptococcosis on either arm (2.5% of the fluconazole group and 5% of the control group) and two patients died, one in each group.…”
Section: Antifungal Prophylaxis For Cryptococcal Meningitismentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent two-year prospective observational cohort study conducted by Sungkanuparph et al [ 87 ] in Thailand, 302 HIV–infected patients who had a CD4 T-cell count < 100 cells/µL and negative serum cryptococcal antigen initiating antiretroviral therapy were enrolled. Five patients developed cryptococcosis on either arm (2.5% of the fluconazole group and 5% of the control group) and two patients died, one in each group.…”
Section: Antifungal Prophylaxis For Cryptococcal Meningitismentioning
confidence: 99%
“…Five patients developed cryptococcosis on either arm (2.5% of the fluconazole group and 5% of the control group) and two patients died, one in each group. This demonstrates that in settings where ART is widely available and HIV-infected patients who have CD4 counts < 100 cells/µL are initiated on ART and are negative for serum cryptococcal antigen, the primary prophylaxis for cryptococcosis with fluconazole has no survival benefit and may not be necessary [ 87 ].…”
Section: Antifungal Prophylaxis For Cryptococcal Meningitismentioning
confidence: 99%
“…In fact, paracoccidioidomycosis is the eighth most important cause of mortality among chronic infectious diseases, reaching rates of 1.65 deaths per 106 inhabitants ( de Oliveira et al, 2015 ). Collectively, these invasive fungal infections are more prevalent in immunocompromised patients ( Woyciechowsky et al, 2011 ; Kaur et al, 2017 ; Sungkanuparph et al, 2017 ). In addition, they are in general also associated with antifungal resistance, making their treatment ineffective for most cases ( Gullo et al, 2013 ; Chowdhary et al, 2014 ; Scorzoni et al, 2017 ).…”
Section: Plant Lectins For Treatment Of Fungal Infectionsmentioning
confidence: 99%
“…After the HAART program became accessible worldwide with a significant reduction of mortality and morbidity in HIV patients, prophylactic therapy for CM became unclear, primarily because of fluconazole resistance and drug interactions [ 22 , 23 ]. Additionally, results from a study conducted by Sungkanuparph et al [ 24 ] concluded that there was no difference in the occurrence of newly diagnosed cryptococcosis between patients with and without primary prophylaxis. None of our 24 patients came to regular visits or blood analysis and all had low adherence to the ARV treatment.…”
Section: Discussionmentioning
confidence: 99%